Audit Quality Of Big Four Firms: Evidence From Client’s Business Strategy - Antonius Herusetya (Universitas Muhammadiyah Malang, 2020)
This study aims to examine the association between audit quality and the client's business strategy using a comprehensive business strategy framework from Miles & Snow (1978; 2003), covering the business strategy of prospectors, defenders, and analyzers. We use the Big Four audit firms as our proxy for audit quality and using a composite score as a construct of a business strategy used by the firms. Using a two-stage logistic regression model in our tests and research samples from public listed companies of manufacturing industries in the Indonesia Stock Exchange (IDX), this study finds evidence that audit quality has a negative effect of the business strategy with prospector-type. This study implies that companies have different business strategies and auditors are more aware of the clients with the prospector-type strategy that increases audit risk and financial statements risk compared to the defender-type strategy. Our study contributes by finding a relation between the audit quality literature and the strategic management literature. Further study should consider broader measures of audit quality instead of the Big Four audit firms.